Pembuktian Eksistensi Dialek Weleri Di Kabupaten Kendal - Menik Lestari; Sri Munawarah (Unit Penelitian dan Publikasi Fakultas Ilmu Budaya Universitas Gadjah Mada, 2021)
An important issue of whether two varieties of language are basically the same or whether they are different dialects or even different languages can be answered using the methods of dialectology. This study looks at the Javanese language used in Kendal regency in Java. People there from the Weleri district attest that their variety of Javanese is a dialect, distinct from the language used by other people in Kendal. There is also literature where the opinion supports this view. But there are also contradictory opinions. This research seeks to provide definitive evidence about the status of the Javanese used by people in the Weleri area, to end any further confusion about its status, one way or the other. The research involved data sampled from many points in the area and the analysis used dialectometry to establish the degree of difference and also interviews to find out what the views of local speakers were. The results were definitive but not without some other interesting facts concerning phatic particles in spoken Javanese coming to light